New species of Pyrgulopsis Call & Pilsbry, 1886 (Mollusca: Caenogastropoda: Hydrobiidae) from two Chihuahuan Desert springs - Perez, Kathryn E.; Hutchins, Benjamin T.; Solis, Megan; Schwartz, Benjamin F. (Zootaxa, 2022)
Two new populations of Pyrgulopsis were found in springs in the Chihuahuan desert region of Texas. Pyrgulopsis Call & Pilsbry, 1886 are a diverse group of snails occupying freshwater springs, usually narrow-range endemics limited to a single spring. Their small ranges confer substantial conservation concern as the drying or disturbance of a single spring can lead to their extinction. We use mitochondrial COI and nuclear LSU sequences, shell morphometrics, and anatomical features to distinguish a new species of Pyrgulopsis endemic to the Big Bend region of Texas.